Implementation of smart anti-theft car security system based on GSM - M. Ahmed, Shakir; M. Marhoon, Hamzah; Nuri, Osman (International Journal of Engineering and Technology, 2019)
Recently, in the last few years, it has been noticed that the theft of cars and the use of stolen cars in suspicious acts by robbers has been increased. The robbers use modern and new methods to theft of different cars. It is therefore necessary to find serious solutions to protect vehicles from theft. In this system the Arduino microcontroller, vibration sensor, GSM SIM 800L module and Bluetooth HC-05 are using to implement the system, the vibration sensor used the purpose of detecting the vibration resulting from the operation of the engine of the car when the vibration detected the message is sent through the GSM unit and the alarm whistle turning “ON” in order to alert the owner of the car. When the car owner wants to operate his car should be entering the secret code to run the car engine through the 4*4 keypad and also requires to send specific command from the smart mobile phone through the Bluetooth to make car engine turning “ON” and otherwise the car does not work, when the thief tries to enter the password more than twice the alarm will be turning “ON” and all cases will appear on the screen of special software was chosen for this purpose all these to make the system reliable and more secure.